2009
DOI: 10.1111/j.1460-9568.2009.06884.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of reelin‐positive plaques is accompanied by a decline in basal forebrain projection neurons during normal aging

Abstract: Besides its critical role during neurodevelopment, the extracellular glycoprotein reelin is also a pivotal regulator of adult synaptic function and plasticity, and altered reelin-mediated signalling has been suggested to contribute to neuronal dysfunction associated with Alzheimer's disease. We have recently discovered, in aged rodents and non-human primates, a pronounced decline in reelin-positive interneurons and concomitant accumulation of reelin in extracellular amyloid-like deposits, both being associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 78 publications
(90 reference statements)
3
33
0
1
Order By: Relevance
“…Further, Reelin is produced by the pyramidal cells of the piriform and entorhinal cortex projecting to thalamus and hippocampus, respectively. In the hippocampus itself, Reelin expression is restricted to local interneurons (Alcantara et al, 1998, Koliatsos et al, 2004, Ramos-Moreno et al, 2006, Knuesel et al, 2009. Finally, Reelin is also expressed in the corticomedial amygdaloid nuclei and the paraventricular nuclei of the thalamus.…”
Section: Reelin Expression Within Olfactory-limbic Pathwaysmentioning
confidence: 90%
See 4 more Smart Citations
“…Further, Reelin is produced by the pyramidal cells of the piriform and entorhinal cortex projecting to thalamus and hippocampus, respectively. In the hippocampus itself, Reelin expression is restricted to local interneurons (Alcantara et al, 1998, Koliatsos et al, 2004, Ramos-Moreno et al, 2006, Knuesel et al, 2009. Finally, Reelin is also expressed in the corticomedial amygdaloid nuclei and the paraventricular nuclei of the thalamus.…”
Section: Reelin Expression Within Olfactory-limbic Pathwaysmentioning
confidence: 90%
“…It would be highly relevant, therefore, to check in the adult brain if oligodendrocytes, which express Reelin in vitro (Siebert and Osterhout, 2011) Importantly, we were recently able to demonstrate that a viral-like prenatal immune challenge predisposes the offspring to develop an AD-like phenotype, which is induced if the challenge is repeated for a second time during adulthood (Krstic et al, 2012a). In these prenatally challenged mice, the loss of Reelin expressing cells (Meyer et al, 2008, Knuesel et al, 2009 coincided with an increase in APP production and cleavage, Tau hyperphosphorylation and missorting, as well as cognitive deficits (Krstic et al, 2012a). This is in agreement with the observations of cognitive decline in aged rats correlating with reduced Reelin expression in the entorhinal cortex (Stranahan et al, 2011a), recently confirmed by the findings of impaired spatial memory following experimental interference with Reelin signaling in the same area (Stranahan et al, 2011b).…”
Section: And Promotesmentioning
confidence: 99%
See 3 more Smart Citations